PERAN PENERIMAAN DIRI DAN DUKUNGAN SOSIAL TERHADAP KONSEP DIRI REMAJA YANG TINGGAL DI PANTI ASUHAN DI BALI - Wulandari, Ayu Ratih; Susilawati, Luh Kadek Pande Ary (Jurnal Psikologi Udayana; Edisi Khusus, 2016)
Adolescence is known as an important period in the formation of self-concept. However, not all adolescents can pass through these phases in the family circle. Adolescents who live in orphanages have certain background which could affect the formation of self-concept. This study aims to determine the role of self-acceptance and social support against self-concept of adolescents living in an orphanage in Bali. This study is expected to provide benefits in the formation of self-concept of adolescents living in the orphanage through the role of self-acceptance and social support. The subjects were 98 adolescents who lived in the orphanage. The sampling technique used a two stage cluster sampling. The results of multiple regression analysis showed (R) of 0.703 (F = 46 318; p < 0.05), which means that self-acceptance and social support jointly contribute to the self concept. The coefficient of determination was 0.494, meaning that effective contribution of self-acceptance and social support in explaining the variant of self-concept as much as 49.4%, and from the value of standardized beta was found that self-acceptance is more a role of self-concept with a value of 0.506 instead of 0.278 social support. It concluded that the role of self acceptance and social support were significantly important against self-concept adolescents living in an orphanage in Bali.   Keywords: Self acceptance, Social Support, Adolescents living in an orphanage.